2013
DOI: 10.1016/j.bbmt.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

An Intermediate Alemtuzumab Schedule Reduces the Incidence of Mixed Chimerism Following Reduced-Intensity Conditioning Hematopoietic Cell Transplantation for Hemophagocytic Lymphohistiocytosis

Abstract: Reduced-intensity conditioning (RIC) improves the outcomes of hematopoietic cell transplantation (HCT) in patients with hemophagocytic lymphohistiocytosis (HLH). Proximal (ie, close to graft infusion) dosing of alemtuzumab is associated with a high incidence of mixed chimerism, whereas distal (ie, distant from graft infusion) dosing is associated with less mixed chimerism but more acute graft-versus-host disease (GVHD). The alemtuzumab dose per kilogram of body weight also influences these outcomes. We hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 25 publications
4
76
4
Order By: Relevance
“…This underscores the need to optimize HSCT to prevent low-level DC (ie, timing, conditioning regimen, donor choice, GVHD, and rejection prophylaxis). 6,7,17 The analysis of the current management approaches in patients with declining DC showed that weaning of immune suppression was started at a median DC of 85% and DLI were applied at a median DC of 45%. As expected, interventions were more frequent in the group of patients in which the lowest DC was #30%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This underscores the need to optimize HSCT to prevent low-level DC (ie, timing, conditioning regimen, donor choice, GVHD, and rejection prophylaxis). 6,7,17 The analysis of the current management approaches in patients with declining DC showed that weaning of immune suppression was started at a median DC of 85% and DLI were applied at a median DC of 45%. As expected, interventions were more frequent in the group of patients in which the lowest DC was #30%.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-three of these patients have been previously reported in articles with a focus on HLH and HSCT, but not on mixed chimerism. 4,[6][7][8]12,[17][18][19] The genetic defects represent the full spectrum of hereditary forms of HLH, including FHL2-5, GS2, XLP 1 and 2, and CHS (Table 1). Most patients had been diagnosed with HLH and received HSCT in the first 2 years of life; however, age at onset and at HSCT ranged until young adulthood.…”
Section: Patient Cohortmentioning
confidence: 99%
“…All patients were treated with an RIC regimen consisting of alemtuzumab, fludarabine, and melphalan as previously described 1,21,22 and received a stem cell graft from a bone marrow (n 5 101) or peripheral blood stem cell (n 5 4) donor. Patients received fludarabine 150 mg/m 2 (1 mg/kg in those weighing ,10 kg) divided over days 28 to 24 or over days 27 to 23 and melphalan 140 mg/m 2 (4.7 mg/kg in those weighing ,10 kg) on day 23 or 22.…”
Section: Transplant Proceduresmentioning
confidence: 99%
“…11 Our patient received a fludarabine-based RIC with both transplants; the rejection observed after first transplant, prepared with alemtuzumab (Table 1, Figure 1), confirmed that DC can result in high risk of engraftment failure. As suggested previously, 12 alemtuzumab administration more distant from graft infusion could allow sufficient T-cell depletion in recipients with less in vivo T-cell depletion of the graft, reducing the risk of rejection and preserving an effective GVHD prophylaxis. In the second transplant, our patient received a higher dose of fludarabine in combination with cyclophosphamide, a single-dose total body irradiation (300 cGy), and antilymphocyte serum (antithymocyte globulin) ( Figure 1B), which may have provided the needed immunosuppression to obtain full donor engraftment without fatal toxicity.…”
Section: Discussionmentioning
confidence: 76%